A NOÇÃO DE IMPERATIVO CATEGÓRICO EM KANT E HUSSERL (Razão e Fé, 2021)
This paper seeks to problematize the processof formulating of the categorical imperative inKant and Husserl. In the first part, the Kant’sconception is reconstructed from the beginningof the Groundwork of the Metaphysics ofMorals until the exposition of the first formulaof the categorical imperative. Along this path,some concepts dear to Kant’s argument arebeing clarified and problematized, such as, forexample, the concepts of good will and duty. Inthe second part, the work seeks to show the originof the formulation of the husserlian categoricalimperative, as well as to understand the role ofthis imperative in the ethical conception of thisauthor. In the final considerations, the intent ofthe work is to highlight the peculiarities pertinentto each proposal and to verify the possibility ofa intersection.